2008
DOI: 10.1007/s00125-008-1168-8
|View full text |Cite
|
Sign up to set email alerts
|

Early loss of mammalian target of rapamycin complex 1 (mTORC1) signalling and reduction in cell size during dominant-negative suppression of hepatic nuclear factor 1-α (HNF1A) function in INS-1 insulinoma cells

Abstract: Aims/hypothesis Mutations in the HNF1A (previously known as TCF1) gene encoding hepatocyte nuclear factor-1α (HNF1A) lead to the development of maturity-onset diabetes of the young, type 3 (HNF1A-MODY), characterised by impaired insulin secretion and a reduction in beta cell mass. HNF1A plays an important role in pancreatic beta cell differentiation and survival. The mammalian target of rapamycin (mTOR) is a central growth factor-and nutrientactivated protein kinase controlling cell metabolism, growth and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
1
14
0
1
Order By: Relevance
“…1, A and B). Previously, we demonstrated a reduction in expression of pyruvate kinase over this time scale after dominant-negative suppression of HNF1A function (8). Indeed, numerous other downstream target genes involved in energy metabolism have been shown to be downregulated 24 h after suppression (9).…”
Section: Expression Of Dn-hnf1a Causes Bioenergetic Dysfunction Inmentioning
confidence: 65%
See 1 more Smart Citation
“…1, A and B). Previously, we demonstrated a reduction in expression of pyruvate kinase over this time scale after dominant-negative suppression of HNF1A function (8). Indeed, numerous other downstream target genes involved in energy metabolism have been shown to be downregulated 24 h after suppression (9).…”
Section: Expression Of Dn-hnf1a Causes Bioenergetic Dysfunction Inmentioning
confidence: 65%
“…In particular, the expressions of the Glut2 glucose transporter and pyruvate kinase have been consistently shown to be reduced by dominant-negative suppression of HNF1A function (2,3,8,9). Mitochondrial targets have also been identified, including decreased expression of the E1 subunit of 2-oxoglutarate dehydrogenase and increased levels of the uncoupling protein UCP2 (2,3).…”
mentioning
confidence: 99%
“…Among the genes identified in this microarray study were several known target genes of HNF1A including Pklr, Foxa3, and Pdk-1, and all were found to be down-regulated in response to Pro291fsinsC-HNF1A (16,17,26,27). Foxa2, which is subject to transcriptional repression by HNF1A (28), was found to be up-regulated.…”
Section: Microarray Analysis Of the Transcriptional Response Of Rat Imentioning
confidence: 99%
“…mTOR complex 1 (mTORC1) and mTOR complex 2 (mTORC2) are two structurally and functionally distinct protein complexes that share mTOR as their catalytic subunit. We have shown that the DN-HNF1A-induced decrease in mTOR signalling correlated with decreased activity of the mTORC1 targets, ribosomal p70S6 kinase and 4E-BP1, and the mTORC2 target, Akt [13].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, we have previously reported that the activity of mammalian target of rapamycin (mTOR), which is negatively regulated by AMPK [12] is suppressed following DN-HNF1A overexpression [13]. mTOR is a serine/threonine protein kinase that integrates nutritional, physiological and hormonal signals within a cell [14,15].…”
Section: Introductionmentioning
confidence: 99%